Strategic Trade Policy Cina di Negara-Negara Sub-Sahara Afrika - Qodarsasi, Umi (State Islamic Institute of Kudus (IAIN Kudus), 2018)
The Strategic Trade Policy of China in Sub-Saharan Africa Countries. In the past decade, Sub-Saharan Africa has been transformed into the 'rising continent'. The growth of the Sub-Saharan economy averages 6%. Some countries in Sub-Saharan are included in the most developed countries in the world. Economic growth, abundant natural resources, and a large population become the potential of Sub-Sahara to become a main trading partner for China as a global economic power. To enhance trade cooperation, China formed a Forum on China-Africa Cooperation (FOCAC). Through this forum, China offers a new development model, namely the Beijing consensus by prioritizing the principle of non-interference. This research aimes to find out the strategic trade policy of China to enhance economic benefits from multilateral cooperation. This research applies descriptive qualitative research method with the strategic trade policy as the research analytical framework. This research finds that China applies some of strategic trade policy in Sub Sahara Africa : sectoral targets, Special Economic Zones (SEZs), liberation of foreign investation, and export subsidies.Keywords: FOCAC Strategic Trade Policy (STP), Sub-Sahara Afrika